A cadaveric porcine corneal wound model using semi-automated assessment - Snyder, Orman Lawrence II (Kansas State University, 2020)
Corneal injuries constitute a major clinical problem in both human and veterinary medicine. Because of this, new methods to improve corneal healing are constantly being developed and tested for safety and efficacy. Historically, corneal injury models utilize rabbits to evaluate therapeutic or toxic compounds, e.g., the Draize test. Animal welfare concerns and the cruelty of live-animal testing have prompted the development of cadaveric corneal injury models. Cadaveric models using rabbits, chickens or pigs are preferred since these animals are slaughtered for food production and thus, intact eyes may be obtained with minimal ethical concerns. In comparison to rabbit and chicken, porcine corneas are anatomically and physiologically more similar to human corneas. For this reason, porcine corneas were tested here. The goal was to develop cadaveric cornea culture, corneal wounding, and assessment methods to enable standardized for preclinical evaluation of novel therapeutics. Two wounding methods were tested here: physical injury and chemical injury. Chemical injury using 0.5 M Sodium Hydroxide (NaOH) for 30 seconds applied using a 7.2 mm filter paper disk produced reproducible corneal epithelial damage. A semi-automated method for wound assessment was developed using a SpectraMax i3 plate reader to measure wound size following fluorescein application. Together, the data show that wound healing occurs for the first 24-48 h after injury and plate reader-based imaging documents wound size in a relatively unbiased manner. These methods lend themselves to testing novel therapeutic agents for safety and efficacy for preclinical evaluation.
Keywords: Cornea; Porcine; Wound; Culture